The Zombie Virus Pandemic: An Innovative Simulation Integrating Virology, Population Health, and Bioethics for Preclinical Medical Students - Jennifer M. Jackson; E Shen; Timothy R. Peters (Association of American Medical Colleges, 2020)
Introduction Understanding population health in the context of infectious disease outbreaks is an important physician competency. However, identifying effective ways to engage early medical students in this content remains a challenge. We designed an innovative pandemic simulation for first-year medical students utilizing the pop culture theme of zombies. Methods This 2.5-hour simulation was conducted in 2018 and 2020 during students' virology course. Student teams collected and analyzed data to formulate hypotheses for the source pathogen. The teams completed reports explaining their diagnostic hypotheses, infection containment recommendations, and resource allocation recommendations. Learners completed an evaluation of the simulation through an online survey. Responses were analyzed using descriptive statistics; narrative responses were analyzed qualitatively for themes. A content analysis was performed on students' reports. Results Two hundred eighty-four medical students participated in this activity. Nearly all respondents agreed that the small-group format (98%, 2018 and 2020) and pace and duration (92%, 2018; 94%, 2020) were appropriate and that the activity was intellectually stimulating (97%, 2018; 96%, 2020). Learner engagement measures were high (90%-97%, 2018; 83%-96%, 2020). Analysis of students' reports revealed evidence of cognitive integration of virology, population health, and bioethics concepts, including integration of new learning content. Discussion Collaborative problem-solving during a simulated zombie-themed pandemic provided preclinical medical students with an engaging opportunity to integrate virology, population health, and bioethics concepts. Implementing this event required advanced planning, use of multiple spaces, learning materials preparation, and recruitment of several faculty, staff, and actors.